Elementary Professional Development within a ‘Practical’ Action Research Effort to Improve Student Literacy - T. G. Ryan; A.M. Aquino; D. Berry; K. Clausen; R.L. Wideman (Networks: An Online Journal for Teacher Research, 2008)
The purpose of this inquiry was to support and augment the action research efforts of elementary teachers who were attempting to enhance literacy outcomes in their respective classrooms. Included are elementary teacher insights, university-based facilitator views, and principal perspectives that together complete a picture of our professional development efforts. Together the data provide an overview of an action research effort, wherein praxis was noted as a necessary element to assume ‘practical’ investigative roles. Praxis herein is the deliberate, informed, planned, and systematic action which is the critical underpinning of all action research efforts. The action in this case was directed towards improvement and implementation of an instructional initiative. This outcome brings with it an immense level of significance in that all educators seek to improve educational outcomes personally, professionally, and politically; therefore a report such as this may be viewed as an essential tool to refine educational practice.